Popularising Sustainable Choices – a deposit system as a socially desirable option - Paattiniemi, Aliisa (My University, 2023)
International climate reports have long stressed that our current way of living and consuming is not sustainable. Action is needed in all sectors to combat the climate change, and different actors such as international organisations, public institutions, private companies and individuals must all be involved in the change (Salmivaara et al. 2020). To address this challenge, the European Union has created a strategy to achieve climate neutrality by 2050, which includes a range of binding legislative measures and non-legislative guidelines to be implemented in the member states (European Commission 2020). As a result, the climate change and EU's actions have been widely discussed in the media and in people's daily lives in recent years. At the same time, however, it has been noted that despite increasing awareness and knowledge, consumer purchasing behaviour has not changed at the same pace (Capstick 2013). This phenomenon is described as the 'green gap', and refers to a situation where, despite green intentions, people do not behave in a sustainable way. This gap between intentions and actual behaviour enables a societal approach to climate change, as it has been noted that green behaviour is often a value debate between one's personal benefits and societal consequences (Jansson & Dorrepaal 2015). This thesis examines the impact of social norms on consumers' pro-environmental purchasing behaviour. Social norms have been found in several studies to influence sustainable behaviour, as they are understood as rules and standards that guide human behaviour (Goldstein et al. 2008; Loschelder et al. 2019; Ryoo et al. 2017). The main research problem of this study was to investigate how social norms guide consumers' pro-environmental purchasing behaviour and, on the other hand, what other factors besides social norms trigger consumers' pro-environmental purchasing behaviour. The study was commissioned by a company that offers a deposit system for takeaway food containers to its customers in Finland, and therefore one of the research problems was also to find out how a pro-environmental deposit system could be turned into a socially desirable option among consumers. The study was conducted using a qualitative research approach and empirical data was collected through five semi-structured interviews. The interviews resulted in the identification of three drivers of pro-environmental purchasing behaviour: environmental consciousness, environmental motivations and contextual drivers. Environmental consciousness was influenced by consumer knowledge, skills and interest in sustainable development issues, while environmental motivations were influenced by attitudes, social norms, motives and emotions. Contextual drivers consisted of availability, user experience and usability.
Keywords: Circular economy, social norms, pro-environmental behaviour, purchasing behaviour, consumer research, green gap